FOLLICULAR THYROID CANCER: COURSE AND TREATMENT - M. A. Engibaryan; Yu. V. Ulyanova; A. A. Barashev (Опухоли головы и шеи, 2015)
The paper gives a clinical observation of follicular thyroid cancer. The latter is frequently indistinguishable from follicular adenoma macroscopically and microscopically, which gives rise to certain difficulties in differential diagnosis and treatment policy. It describes a rare case of a contralateral metastasis from follicular thyroid cancer to the tubular bone with a long history of the disease and indicates the complexity of pre-, intra-, and postoperative diagnosis and the possibilities of surgical treatment.